2019
DOI: 10.1007/s10637-019-00783-7
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib study of GSK3052230, an FGF ligand trap in combination with pemetrexed and cisplatin in patients with malignant pleural mesothelioma

Abstract: is an employee of MSKCC and MSKCC has an institutional collaboration agreement with IBM for Watson for Oncology and receives royalties from IBM, is the Chair of the Board of Directors of the Mesothelioma Applied Research Foundation, reports receiving commercial research grants from MedImmune, Epizyme, Polaris, Sellas Life Sciences, BMS, and Millenium, and is a consultant/advisory board member for Epizyme and Aldeyra Therapeutics. J.F. Vansteenkiste reports receiving research funding/honoraria from MSD, AZ, BMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“… 80 Further studies combining FP-1039 with pemetrexed and cisplatin in mesothelioma patients and with paclitaxel and carboplatin in patients with FGFR1 -amplified non-small cell lung cancer have also been completed. 81 , 82 …”
Section: Fgfr-targeted Therapiesmentioning
confidence: 99%
“… 80 Further studies combining FP-1039 with pemetrexed and cisplatin in mesothelioma patients and with paclitaxel and carboplatin in patients with FGFR1 -amplified non-small cell lung cancer have also been completed. 81 , 82 …”
Section: Fgfr-targeted Therapiesmentioning
confidence: 99%
“…Marek et al found a link between high FGFR1 protein expression determined by immunoblotting in MPM cell lines and sensitivity to the FGFR inhibitors ponatinib and FP1039/GSK3052230 [10]. The latter inhibitor was recently tested in a phase Ib study in MPM [38]. Quispel-Janssen et al reported that loss of BAP1 was linked to increased FGFR inhibitor sensitivity and elevated FGFR/FGF expression in MPM cells [15].…”
Section: Discussionmentioning
confidence: 99%
“… 79 High-throughput drug sensitivity testing of a panel of commercial and primary early passage mesothelioma cell lines identified a subgroup of MPM lines highly sensitive to FGFR inhibition as well as death receptor agonist tumour necrosis factor-related apoptosis-inducing ligand (TRAIL), associated with BAP1 loss. 80 81 A phase Ib clinical trial of a FGF ligand trap in combination with pemetrexed/cisplatin chemotherapy appeared to show durable responses, 82 but further validation is required before loss of BAP1 can be used as a biomarker for responsiveness to FGF/FGFR inhibitors or TRAIL.…”
Section: Two-dimensional Culture Of Human Pleural Mesothelioma Cellsmentioning
confidence: 99%